2008
DOI: 10.1007/bf03175335
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification and phylogenetic status of marineBacillus associated with coral sediment, showing antibacterial effects against human pathogens

Abstract: Ninety-three strains were collected from coral reef sediments and artificial mangrove forest in south India and screened for antibacterial property by cross-streaking assay against 11 human pathogens. Five different fractions of three positive strains (GM4, GM5 and GM10) were prepared and culture filtrate (CF), ethyl acetate extracts (EA) and intermediate opaque layer (IOL) fractions showed antibacterial activity against Pseudomonas aeruginosa, Staphylococcus aureus, Salmonella enterica, Bacillus sp. and Prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…P8 inhibits both Gram+ and Gram- pathogens. This finding is supported by other studies such as those of Chatterjee et al ( 2008 ) and Prieto et al ( 2012 ) who reported antibacterial activities of Bacillus strains isolated from reef sediments and marine alga against P. aeruginosa, S. aureus, Salmonella enterica, Bacillus sp., Proteus vulgaris, E. coli , and S. typhimurium . Gram negative isolates such as Pseudomonas and Pseudoalteromonas strains (P9, P10, P11, and P20) have variable antibacterial activities toward both Gram+ and Gram− tested pathogens.…”
Section: Discussionsupporting
confidence: 87%
“…P8 inhibits both Gram+ and Gram- pathogens. This finding is supported by other studies such as those of Chatterjee et al ( 2008 ) and Prieto et al ( 2012 ) who reported antibacterial activities of Bacillus strains isolated from reef sediments and marine alga against P. aeruginosa, S. aureus, Salmonella enterica, Bacillus sp., Proteus vulgaris, E. coli , and S. typhimurium . Gram negative isolates such as Pseudomonas and Pseudoalteromonas strains (P9, P10, P11, and P20) have variable antibacterial activities toward both Gram+ and Gram− tested pathogens.…”
Section: Discussionsupporting
confidence: 87%
“…In our previous study also, a number of bacteria were isolated from same coral reef ecosystems with potent antibacterial activity against a series of human pathogens [7]. A report on another aquatic ecosystem indicated that V. harveyi and some related vibrios isolated from shrimp larvae were resistant to erythromycin, kanamycin, penicillin G, and streptomycin [4].…”
Section: Discussionmentioning
confidence: 96%
“…Even at the base of the live coral reef, where algal attachment was more, TBC was found to be more as compared to the upper surface of coral reef where polyps were very active. This might be due to the fact that corals have their own deterrent mechanism to prevent attachments of external bacteria by producing antibacterial compounds and other bioactive substances [7].…”
Section: Discussionmentioning
confidence: 99%